Analisis Implementasi Kebijakan Verifikasi Dukungan Pencalonan Bakal Calon Perseorangan Pada Pemilukada Kabupaten Labuhanbatu Tahun 2020 - Fairouz Moehammad; Tonny P. Situmorang; Hatta Ridho (PERSPEKTIF, 2022)
The purpose of this paper is to analyze the implementation of policies in the verification of individual support requirements at the Labuhanbatu Regency KPU in the 2020 post-conflict local election and describe the factors that become obstacles in the policy implementation process in the process of verifying the support requirements of individual candidates in the 2020 post-conflict local election. This study uses qualitative research methods. The type of research is descriptive qualitative where the researcher describes the data obtained as a result of a study. By using this method, the researcher will get the data as a whole and can be described clearly so that the results of this research are really in accordance with the existing field conditions. Researchers explore all about the mechanism of the Labuhanbatu Regency KPU in the registration and verification stages of the support requirements of individual candidates in the 2020 Regional Head Election without any manipulation and will present data according to field conditions that occurred at that time.